Effects of Biodynamic Vineyard Management on Yeast Community and Aroma Components in ‘Cabernet Sauvignon’ Wine - CHEN Xuelian, ZANG Wei, LIU Yu, JIANG Zhanzhan, PENG Shuai, WANG Jing (Shipin Kexue, 2023)
In order to explore the effects of biodynamic vineyard management on the yeast community structure and volatile aroma components during wine fermentation, Cabernet Sauvignon grapes from biodynamic (BD) and conventional (CV) vineyards were naturally fermented, and the composition and succession of yeast community and aroma components were analyzed during the fermentation process, and the correlation between yeast communities and aroma components was analyzed by redundant analysis (RDA). The results showed significant differences in the yeast community composition between the BD and CV samples at different fermentation stages. At the early stage, Hanseniaspora uvarum, Starmerella bacillaris, Pichia kudriavzevii, Issatchen kiaorientalis and Cryptococus flavescens were the dominant species in BD, while H. uvarum, Metschnikowia pulcherrima and C. flavescens were the dominant species in CV. As the fermentation proceeded, the yeast species in BD and CV increased to 9 and 7 at the middle stage, respectively. H. uvarum was the dominant yeast in both samples. The non-Saccharomyces species decreased at the later and final stages of fermentation, Saccharomyces cerevisiae gradually became the dominant species, but Hanseniaspora opuntiae and S. bacillaris were found in CV but not BD at the end of fermentation. During the alcoholic fermentation process, the total content of aroma compounds was significantly higher in BD than in CV. Meanwhile, at all stages of fermentation, the contents of alcohols, aldehydes, and terpenes were higher in BD than in CV. However, the content of esters was lower in BD than in CV. RDA analysis showed that S. cerevisiae was positively correlated with the contents of all characteristic aroma components except benzaldehyde, and non-Saccharomyces yeasts (H. opuntiae, P. kudriavzevii, etc.) were positively correlated with the contents of 1-hexanol, benzaldehyde and ethyl acetate. In summary, this study provides data support for understanding the influence of different vineyard managements on the microbial diversity of vineyard and the aroma quality of grape and wine.